Pengaruh Berbagai Media Tanam Dan Pemberian Mikro Organisme Lokal (MOL) Keong Mas Terhadap Pertumbuhan Dan Produksi Tanaman Bawang Tiwai (Eleutherine americana ) - Sumarno Sumarno; Mahdalena Mahdalena; Hamidah Hamidah (Agrifarm : Jurnal Ilmu Pertanian, 2016)
Onions Tiwai is one plant in Borneo forest used by people as a traditional medicine. One of the efforts to support increased production of onions tiwai is through the cultivation of technology media including by the use of appropriate planting and the provision of the Micro Organisms Local (MOL). The aim of research to know the influence of MOL conch mas on growth and yield of onion tiwai and to determine the best planting medium for the growth and production of onions tiwai. The study was conducted over four months starting from nursery seedlings until harvest. This study uses a randomized block design (RBD) with a 4 x 4 factorial experiment consisting of three replications. The first factor is the Growing Media which comprises four levels: ie m0 (Control), m1 (Topsoil and sand), m2 (Topsoil and Rice Husk) and m3 (Topsoil, Rice Husk and Sand). The second factor is the concentration of microorganisms Local (MOL) snails consists of four levels ie p0 (control) p1 (100 ml / liter water) p2 (200ml / liter of water) and p3 (300 ml / liter). The results showed that treatment of the planting medium (M) significantly affected the parameters of the number of leaf age 60 DAP and is not significantly affected, plant height, number of tillers, the number of bulbs, tubers and the weight of the growing media pH. While the provision of MOL Keong Mas (P) had no significant effect on all parameters. There is no interaction between the treatment plant and the provision of various media MOL Keong Mas on all parameters observed.